2014
DOI: 10.11648/j.aff.20140305.18
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Apiculture in Watershed Management and Income Improvement in Galessa Protected Area, Ethiopia

Abstract: Beekeeping gives local people economic incentive for the preservation of natural habitats and is an ideal activity in watershed conservation program. The study was designed to assess and demonstrate the contribution of improved beekeeping for income generation and sustainable watershed management in Galessa protected area. For this purpose households were purposively selected based on their interest in beekeeping, experience in traditional beekeeping and proximity of residence to watershed areas. Training on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Emerging practices of integration of apiculture with watershed protection projects [4, 9], the recognition of the contribution of crop plants pollination [2, 3, 10] and the location of BSNP at the upper watershed relative to the Great Renaissance Dam Project site implicates the significance of the bee forage species diversity in BSNP for initiating apiculture-related development projects. Sixty seven (19 %) species grouped in 60 genera and 41 families were locally perceived as more valuable bee forage plants (Appendix 1) than the remaining species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Emerging practices of integration of apiculture with watershed protection projects [4, 9], the recognition of the contribution of crop plants pollination [2, 3, 10] and the location of BSNP at the upper watershed relative to the Great Renaissance Dam Project site implicates the significance of the bee forage species diversity in BSNP for initiating apiculture-related development projects. Sixty seven (19 %) species grouped in 60 genera and 41 families were locally perceived as more valuable bee forage plants (Appendix 1) than the remaining species.…”
Section: Resultsmentioning
confidence: 99%
“…In the dendrogram at linkage distance 25, two cluster solutions separate two groups [3, 14, 2, 12, 5, 6] and [8, 9, 4, 13, 7, 11, 1, 10] from influences of environmental proximity and a combination of other factors. Key informants [3, 14, 2, 12] live close to the margins of the TIKUR DEN vegetation while [8, 9, 4, 13, 7, 11, 1, 10] close to the GUASSA vegetation. But astonishingly, key informants 5 and 6 of the GUASSA group aligned differently in their responses with the TIKUR DEN vegetation group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals, households, and communities are more likely to accept or invest in activities that enable land rehabilitation over a long period of time, if there are immediate economic incentives to invest (Mekuria et al, 2020). In this line, Ethiopian and Kenyan studies (Kifle, Hora, & Merti, 2014;Wairore, Mureithi, Wasonga, & Nyberg, 2016) demonstrated short-term benefits from exclosures can be enhanced through integrating beekeeping and livestock production. The IAD framework also suggested that costs and benefits assigned to an intervention dictate the interaction and exchange of goods and services among participants.…”
Section: The Action Situationsmentioning
confidence: 99%